Firms' strategies for knowledge and technology transfer with public research organisations and their impact on firms' performance: An empirical analysis based on firm-level data - Spyros Arvanitis; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2006)
Based on a representative firm sample for Switzerland we empirically investigated strategic approaches for knowledge and technology transfer (KTT) activities between business firms and public research organisations. Based on cluster analysis of 19 different forms for KTT, three types of KTT strategies were identified, each of them correspond with a specific combination of some of the 19 different forms for KTT activities. It was found that they are determined mainly by variables related (a) to the absorptive capacity of a firm and (b) to the degree of appropriability of the returns of innovation, indicating that the followed strategy reflects the resource base of a firm. Further, it was shown that a firm's obstacle profile with respect to KTT activities is related to the applied strategy. Firms with more intensive contacts emphasise risk-related factors and financial restrictions, while firms with less intensive contacts emphasise a mismatch between firm and university requirements with respect to KTT. Furthermore and most importantly, it was found that strategy matters for the impact of KTT on the innovation performance of a firm. In fact, KTT strategies related to the core R&D activities of a firm showed a greater impact compared to strategies related to softer forms of transfer activities, e.g. informal contacts or education related contacts.
Keywords: O30; 330; R&D strategies; knowledge and technology transfer; innovation activities; R&D activities